Effects among healthy subjects of the duration of regularly practicing a guided imagery program - Shirakawa Taro; Fukuda Sanae; Watanabe Eri (BMC, 2005)
Abstract Background We examined a large number of healthy adults in the general community who had individually participated in a guided imagery (GI) program daily and for various durations, to examine the psychophysiological effects of a GI program within a healthy group. Methods We studied 176 subjects who had participated in sessions that were part of a guided imagery program, and who had practiced GI at home for 20 minutes once daily in a quiet place after mastering GI in the group sessions. The average duration of GI practiced at home was 6.88 ± 14.06 months (n = 138, range: 0 to 72). The Multiple Mood Scale (MMS), Betts (1909) Shortened Questionnaire on Mental Imagery (QMI), and a visual analog scale (VAS) of imagery vividness, salivary cortisol (CS) levels, general stress and general health were used in the sessions. Results We examined the relationship between the duration of daily GI practiced at home and MMS, QMI, CS, general health, and general stress at baseline. The subjects who had practiced GI at home longer had lower negative mood scores at baseline and lower severity of stress, and higher positive mood at baseline (both at a session and at home), general health, and QMI scores at baseline. The MMS change during a session and the duration of daily GI practiced at home were not correlated. Repeated-measures analysis of covariance showed that the duration of daily GI practiced as the covariate was not associated with changes in the three CS levels. Conclusion Although regularly practicing a GI program daily for 20 min did not affect the CS level or mood during a GI session for several hours, it kept a good condition of the general mental, physical well-being and their overall stress of the practitioners as they had practiced it for long duration. We postulate that subjects who have the high ability of imaging vividness showed the better mood, health status and less stress than those subjects who have the low ability of it did. The ability of image vividness of the long-term regular practitioners of GI was higher than its short-term or inexperienced practitioners, which allowed practitioners to produce more comfortable imagery. Consequently, the longer the duration that they had practiced GI program once a day regularly, the lower scores of their stress were and the higher scores of their health were. We suggest that the regular daily practice of a GI program might be connected to less stress and better health.